The impact of human immunodeficiency virus‐related diseases on pigmented skin types. (4th October 2013) - Ameen, M.
Abstract : What's already known about this topic? Infection with human immunodeficiency virus (HIV) remains a significant problem globally. HIV infection is associated with a wide range of skin disorders. Clinical presentation varies in pigmented skin types. What does this study add? An overview of the common HIV‐related skin diseases with emphasis on differences in darker skin types. Summary: Infection with human immunodeficiency virus (HIV) remains a significant problem globally. Early diagnosis and treatment with antiretroviral drugs has considerably improved health outcomes and decreased disease‐related morbidity. HIV infection is associated with a wide range of skin disorders enabling dermatologists to diagnose HIV as well as associated opportunistic infections early in the course of disease. Despite concerted efforts by international health organizations to limit disease incidence, the prevalence of HIV infection remains high and is highest in sub‐Saharan Africa. The diagnosis of HIV‐related skin diseases is challenging as immunosuppression often results in atypical disease presentation. In addition, the clinical presentation will vary in pigmented skin types. The aim of this article is to describe disease variation in pigmented skin types.